GEL CONTENDO EXTRATO DE Ilex paraguariensis A. St. Hil. PARA USO CONCOMITANTE AO LED NA RECUPERAÇÃO DE LESÕES DE SEGUNDA INTENÇÃO - Bini, Ana Carolina Dorigoni (2021)
Wound Healing is a complex and dynamic process that can be divided into phases with the goal of restoring damaged tissue and return it to homeostasis. The use of photobiomodulation can be effective in the healing of tissues, highlighting the use of LED in tissue repair. Ilex paraguariensis A. St. Hil. (Aquifoliaceae), popularly known as mate (erva-mate), is an herb specie native to southern Latin America, where it is commonly used as a tea and has great economic and social importance. In its chemical composition, there are bioactive compounds, with emphasis on compounds with antioxidant activity. The present study aimed to develop a gel for incorporating the Ilex paraguariensis extract and to verify the effects of applying the Ilex gel associated with the 627 nm LED, comparing it with the application of the gel and LED alone in the healing process in an experimental model. Thus, a 3% sodium carboxymethyl cellulose gel was developed associated with the extract of Ilex paraguariensis at 5% concentration; the chosen concentration of the polymer was ideal to achieve the desired spreadability of the product as it had the adequate viscosity. Regarding the rheological characteristics, the gel showed a non-Newtonian pseudoplastic profile. The in vivo evaluation was performed using a dorsal punch model. The sample consisted of 96 Rattus Norvegicus rats, Wistar lineage, divided into 4 groups: control group (CG) with tissue damage and application of the base gel, but without irradiation; LED group (GL) with tissue damage, application of the base gel and irradiation by LED 627 nm; LED + ILEX (GLIL) group with tissue damage, application of Ilex gel and irradiation by LED 627 nm; and ILEX group (GI) with tissue damage and application of the Ilex gel. All groups were subdivided into 3, 7, 14 and 21 days. The application method was punctual and perpendicular to the skin surface, with irradiation times of 60s, which corresponds to a dose of 7 J / cm2. Analysis of the contraction of the lesion, histological analysis, analysis of total collagen using polarized light microscopy and immunohistochemical analysis were performed. The data obtained were analyzed statistically. In the macroscopic analysis of wound contraction, it was found that LED and Ilex provided complete epidermal regeneration after 21 days of treatment, but the treatment with Ilex showed scarring remnants. The histological analysis revealed that the Ilex 9 associated with the LED and LED groups showed better healing in relation to the other groups in all the analyzed periods. An organization of the epidermis, no crust, and absence of inflammatory infiltrate were observed. In the analysis by polarized light, the groups treated with Ilex and Ilex associated with LED obtained an acceleration of the tissue regeneration process and proliferation of type I collagen in all the analyzed periods, and the group that was only treated with LED had a better proliferation of collagen at 14 and 21 days. In the immunohistochemical analysis, it was observed in all treated groups that the expression of VEGF-α and TGF-β1 were higher in the first days of treatment compared to the control groups, indicating that the healing process in these groups was accelerated. It is concluded that the CMC polymer at 3% showed superior viscosity characteristics and was more appropriate for the development of the gel containing Ilex paraguariensis for use with wound healing purposes. The 627 nm LED and the Ilex paraguariensis gel were effective in healing epidermal wounds in an animal model where both therapies have shown promise for the use intended for the healing of skin lesions, but some limitations regarding the associated use of therapies are still seen, that did not generate the optimized healing effect expected. It is suggested to adjust the concentration of the Ilex paraguariensis extract in future studies to see if its effects can become superior.